(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2022)
Academic freedom is fundamental to the formation of a knowledge society. It is a form of freedom that needs to be upheld and strengthened to ensure that the the delivery of knowledge can continue to be implemented transparently and openly. However, this freedom has become a hot topic of discussion in society because there are restrictions against the development of knowledge which lead to non-sustainability of the educational sector. The Federal Constitution, the Statutory Bodies (Discipline and Surcharge) Act 2000 (Act 605), the University and University Colleges Act 1971 (Act 30), Education Act 1996 (Act 550), Private Higher Educational Institutions Act 1996 (Act 555), National Council on Higher Education Act 1996 (Act 546), Malaysian Qualifications Agency Act 2007 (Act 679) and the constitutions of the various universities are among the series of important statutes that need to be debated in detail, so that matters related to academic freedom in Malaysia can be clearly defined and put back on track. The objective of this article is to discuss those legal provisions which are directly or specifically related to academic freedom, especially involving those academics currently serving in higher education institutions in Malaysia. As an immediate effect of this article, it can be stated that there are several provisions of the said statutes which need to be reviewed immediately in order to ensure that the aspirations and goals of the National Education Philosoph—to produce holistic and integrated human capital in meeting the challenges of the globalization era—can be realized effectively. Keywords: Federal Constitution, National Education Philosophy, restrictions, education, academic freedom, human capital Full text: PDF